Modal Sosial dalam Keterpilihan Perempuan Calon Gubernur: Studi Kasus Karolin Margret Natassa di Kalimantan Barat dan Khofifah Indar Parawansa di Jawa Timur pada Pilkada Serentak 2018 - Nawang Wungu, Dewi Arum (Universitas Brawijaya, 2022)
This thesis aims to see how social capital is utilized in the process of selecting female gubernatorial candidates in the 2018 election. The research subjects were Karolin Margret Natassa of West Kalimantan and Khofifah Indar Parawansa of East Java. This phenomenon needs to be studied through a constructive paradigm, to find out how these two women formed and used their social capital to win as governors, a position that has rarely been filled by women since the direct local election era began. A social capital analysis is placed at the micro (individual) level in the structural (network) dimension using the Social Capital theory of Pierre Bourdieu and Robert Putnam. This research also wanting to identifies what kind of political pathways lead women into political contestation, and how it can affect the instrumentalization pattern of their social capital. The research procedure was carried out using qualitative methods where data collection was carried out through in-depth interviews with key informants and then deepened by literature studies. The results showed that Karolin and Khofifah have different types of social network ties in the process of utilizing their social capital. Karolin is a Bonding type (Same identity with strong ties characteristic and more focusing on internal traits), while Khofifah is a Bridging and Linking type, where the earned trust is used to bridge the interests of groups and later to be activated as a ladder to her political interests. The results of the study also identified Karolin as a politician from the elite route and Khofifah as a politician from the grassroots route.